Van der Waals SnSe2(1−x)S2x Alloys: Composition‐Dependent Bowing Coefficient and Electron–Phonon Interaction. (9th January 2020) - Kudrynskyi, Zakhar R.; Wang, Xueting; Sutcliffe, Jake; Bhuiyan, Mahabub A.; Fu, Yuhao; Yang, Zhuo; Makarovsky, Oleg; Eaves, Laurence; Solomon, Andrij; Maslyuk, Volodymyr T.; Kovalyuk, Zakhar D.; Zhang, Lijun; et al.
Abstract: The design of advanced functional materials with customized properties often requires the use of an alloy. This approach has been used for decades, but only recently to create van der Waals (vdW) alloys for applications in electronics, optoelectronics, and thermoelectrics. A route to engineering their physical properties is by mixing isoelectronic elements, as done for the SnSe2(1− x ) S2 x alloy. Here, by experiment and first‐principles modeling, it is shown that the value of x can be adjusted over a wide range, indicating good miscibility of the SnS2 and SnSe2 compounds. The x ‐dependence of the indirect bandgap energy from E ind = 1.20 eV for SnSe2 to E ind = 2.14 eV for SnS2, corresponds to a large bowing coefficient b ≈ 1 eV, arising from volume deformation and charge exchange effects due to the different sizes and orbital energies of the S‐ and Se‐atoms. This also causes composition‐dependent phonon energy modes, electron–phonon interaction, and temperature dependence of E ind . The alloys are exfoliable into thin layers with properties that depend on the composition, but only weakly on the layer thickness. This work shows that the electronic and vibrational properties of the SnSe2(1− x ) S2 x alloy and its thin layers provide a versatile platform for development and exploitation. Abstract : Exfoliable SnSe2(1− x ) S2 x van der Waals alloys are investigated by experiment and first‐principles modeling, showing that the value of x can be adjusted over a wide compositional range, which indicates good miscibility of the SnS2 and SnSe2 compounds. The present work demonstrates that the electronic and vibrational properties of this alloy provide a versatile platform for further developments and exploitation.